2020
DOI: 10.2147/cmar.s253760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Acquired <em>T790M</em> Mutation in Patients Failing First- or Second-Generation <em>Epidermal</em> <em>Growth</em> <em>Factor</em> <em>Receptor</em>-Tyrosine Kinase Inhibitors</p>

Abstract: Background This study aims to determine the predictors of acquired exon 20 T790M mutation in advanced non-small cell lung cancer (NSCLC) patients harbouring sensitizing epidermal growth factor receptor ( EGFR) mutation following the failure of first- or second-generation EGFR -tyrosine kinase inhibitor (TKI). Methods This is a retrospective observational study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Generally, pretreatment of individuals harboring the exon 19 deletion is associated with a higher risk of developing the acquired T790M resistance mutation than pretreatment of individuals harboring the L858 mutation [ 22 ]. In addition, the clinical tumor response [ 23 ] and a longer duration of EGFR-TKI treatment (≥12 months) [ 24 , 25 , 26 , 27 ] were reported to be associated with a higher frequency of T790M mutation acquisition. Therefore, patients in the low-risk groups with predicted PFS ≥12 months may be presumed to have a higher chance of acquiring the T790M mutation and are suitable for sequential osimertinib use, although acquired T790M and sequential osimertinib were not evaluated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, pretreatment of individuals harboring the exon 19 deletion is associated with a higher risk of developing the acquired T790M resistance mutation than pretreatment of individuals harboring the L858 mutation [ 22 ]. In addition, the clinical tumor response [ 23 ] and a longer duration of EGFR-TKI treatment (≥12 months) [ 24 , 25 , 26 , 27 ] were reported to be associated with a higher frequency of T790M mutation acquisition. Therefore, patients in the low-risk groups with predicted PFS ≥12 months may be presumed to have a higher chance of acquiring the T790M mutation and are suitable for sequential osimertinib use, although acquired T790M and sequential osimertinib were not evaluated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…of cases. 19,20 In this study, blood-based NGS testing revealed the acquisition of T790M. Osimertinib, a thirdgeneration EGFR-TKI, has demonstrated high efficacy in patients with T790M-positive advanced NSCLC in whom disease had progressed during prior first-or secondgeneration TKI therapy.…”
Section: Dovepressmentioning
confidence: 83%
“…In the multivariate analysis of molecular and clinical predictors, the presence of EGFR Ex19del mutations (vs Ex21 L858R mutations), younger age (< 65 years), the absence of metastases (brain or intrathoracic lymph nodes), and lower fluorodeoxyglucose (FDG) uptake on FDG-PET/CT imaging (indicative of lower metabolic rate of viable tumor cells) were independently associated with a higher probability of acquiring T790M mutation following treatment failure on first- or second-generation EGFR TKIs. 117 - 120 In addition, Chua et al conducted an in-depth analysis of genetic and transcriptome alterations shaping the EGFR TKI resistance trajectories. The study results showed that the presence of TP53 wild-type, aging mutational signatures, and the absence of whole-genome doubling were predictive for the emergence of T790M-positive resistance.…”
Section: Factors Influencing the Selection Of Frontline Therapy In As...mentioning
confidence: 99%